Preparation of adhesive using soy protein and lignin - Ng Yit Hui, Alicia (2014)
Abundant, renewable and inexpensive soybean can be a good alternative to natural adhesive. Soy flour was modified by repeated digestion of soy flour by sodium hydroxide and hydrochloric acid. 5%, 10% and 20% modified soy flour (MSF) was then prepared. Medium density fibreboard (MDF) of 810 kg/m3 was made using wood fibre and thickness swelling properties and mechanical properties were analyzed to determine the performance of the board. In the second part, the MSF concentration with the best mechanical result was used to prepare MSF with enzymatic hydrolase lignin (EHL) of that particular concentration. Laccase enzyme was added to 5% lignin to produce EHL. Thickness swelling and mechanical properties were analyzed to determine the performance of the board. FTIR and DSC analysis were performed to understand the structure and properties of all the different types of adhesive. Thickness swelling test exhibit that 5% MSF showed the least thickness swelling. However it did not meet the requirement of ASTM. 10% MSF with EHL did not show a better result either as it increased to more than 100%. For mechanical testing, internal bonding for 10% MSF showed the best result and it almost reached the ASTM standard. 10% MSF with EHL also showed similar result as the 10% modified soy flour. As for modulus of rupture, 10% MSF also had better results. However, both 10% MSF and MSF with lignin had results that were passing the ASTM standard